Partnering with the Devil: The Rationality of the Qur'an on the Use of Charms by Muslim Traders in Selawan Village, Asahan, North Sumatra - Nurdila, Siti; Abbas , Mardhiah (Jurnal Semiotika Quran, 2024)
This study explores the practice of using business charm by Muslim traders in Selawan Village, Asahan Regency, as a tradition in the business world that is carried out from generation to generation and has become a cultural heritage among traders. The method used is a case study using primary and secondary data collected through semi-structured interviews. The findings explain that the use of penglaris begins with the reading of verses from the Qur'an accompanied by certain rituals, such as burning kemenyan and incense, as a form of effort to "cleanse" the shop or merchandise from negative influences. The use of business charm is considered a strategy to compete in the business world by partnering with supernatural beings. The ritual is believed to be able to generate profits and attract more buyers,  although the  quality  of  the  goods sold  sometimes does not meet the best standards. The phenomenon of the use of business charm by traders emphasizes the dynamics of business competition in society, where belief in objects that have been read verses from the Qur'an is considered in line with Islamic teachings. However, on the other hand, this practice raises controversy because it can conflict with Islamic principles that prohibit excessive belief in mystical or supernatural elements.